Spiral structure in galaxies - Seigar, Marc S. (IOP (Series). Release 3., 2017)
How does it happen that billions of stars can cooperate to produce the beautiful spirals that characterize so many galaxies, including ours? This book reviews the history behind the discovery of spiral galaxies and the problems faced when trying to explain the existence of spiral structure within them. In the book, subjects such as galaxy morphology and structure are addressed as well as several models for spiral structure. The evidence in favor or against these models is discussed. The book ends by discussing how spiral structure can be used as a proxy for other properties of spiral galaxies, such as their dark matter content and their central supermassive black hole masses, and why this is important.